PERFORMANCE OF WIRELESS POWER TRANSFER WITH VARIOUS RECEIVER POSITIONS BY - Yusniati, Yusniati; Herman, A.; Fitra, M.; Fareq, M.; Irwanto, M.; Mahrizal, M. (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2015)
In this paper, we have study performance of wireless power transfer with various receiver positions are 00, 900, and 1800 developed transmitter, receiverÂ  and 2 structure magnetic resonant couplings. Both of the Transmitter and Receiver couplings are made of enamel coil. Â Based on experimental performance of wireless power transfer with various receiver positions by using inductive coupling no effect tilted at 00, 900, and 1800Keywords: Tilted, Power Transfer